2019
DOI: 10.21043/aktsar.v2i2.5850
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pengungkapan Islamic Social Reporting (ISR) Terhadap Kinerja Keuangan Pada Perbankan Syariah Di Indonesia Tahun 2012-2016

Abstract: This study aims to examine the influence of Islamic Social Reporting (ISR) disclosure on financial performance. The dependent variable used in this research is financial performance measured by Return on Asset (ROA) and Return on Equity (ROE). The independent variable in this research is The Islamic Social Reporting (ISR). This study uses firm size as a control variable. The population in this study is the sharia banking industry registered in the Financial Services Authority (OJK) period 2012-2016. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
4
0
2
Order By: Relevance
“…Besides, the development index of ISR disclosure in Indonesia is relatively slower than that of ISR disclosure in other Islam countries. This issue is supported by a number of studies in Indonesia revealing that the average of ISR disclosure is low, that is, about 50% (Retnaningsih et al, 2019;Widiyanti and Hasanah, 2018). It may be caused by the absence of standard or regulations which can be adopted by companies in implementing ISR disclosure.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, the development index of ISR disclosure in Indonesia is relatively slower than that of ISR disclosure in other Islam countries. This issue is supported by a number of studies in Indonesia revealing that the average of ISR disclosure is low, that is, about 50% (Retnaningsih et al, 2019;Widiyanti and Hasanah, 2018). It may be caused by the absence of standard or regulations which can be adopted by companies in implementing ISR disclosure.…”
Section: Introductionmentioning
confidence: 98%
“…ISR is a collection of social responsibility reporting indicators set by AAOFII that are compliant with Sharia (Nurhayati & Rustiningrum, 2021) and further developed by researchers (Haniffa, 2002;Maali et al, 2006;Ousama andFatima, 2006 andOsman et al ., 2009). Retnaningsih et al (2019) found that ISR had an impact on the financial performance of the banking sector. Johan Arifin and Eke Ayu Wardani (2016) stated that their research shows that ISR disclosure activities in financial statements have a large positive influence on the financial performance of the banking sector.…”
Section: The Influence Of Islamic Social Reporting On the Maqashid Sh...mentioning
confidence: 99%
“…Many types of research on Islamic social reporting have been carried out, among others, Adisaputra (2021), Arshad et al (2012), Fildjah & Nurdin (2019, Mardliyyah et al (2020), Nadila &Annisa (2021), andRetnaningsih et al (2019) which found that Islamic social reporting had a positive effect on banking performance. This means that more disclosures of the ISR Index in banking companies will improve the performance of the banking sector.…”
Section: The Development Of Islamic Commercialmentioning
confidence: 99%
“…Hal ini memiliki makna bahwa kemampuan suatu bank dalam menghasilkan laba tidak dipengaruhi oleh aktifitas sosial yang dilakukan oleh bank itu sendiri. Namun hasil penelitian ini tidak sejalan dengan penelitian Retnaningsih, Hariyanti, and Astuti (2019); Adisaputra and Kurnia (2021) yang menyatakan bahwa ISR berpengaruh terhadap kinerja keuangan.…”
Section: Pengaruh Isr Terhadap Financial Performanceunclassified